Effective Strategies in Managing Educational Financing for Islamic Higher Education Institutions in the Contemporary Era - Supriatna, Dasep (AGUSPATI Research Institute, 2025)
This study examines effective strategies for managing educational financing in Islamic higher education institutions, emphasizing adherence to Islamic finance principles[3] and addressing contemporary challenges. Utilizing a mixed-methods approach, the research explores waqf revitalization[1], sukuk implementation[2], revenue diversification, and stakeholder engagement[4] as mechanisms to enhance financial sustainability and ethical alignment. Findings reveal that institutions leveraging waqf and sukuk demonstrate improved financial resilience and reduced reliance on tuition fees. Stakeholder collaboration and capacity-building initiatives[8] emerge as critical elements for optimizing financial strategies, ensuring accessibility, and advancing institutional missions in alignment with Shariah principles.